Kewenangan Majelis Permusyawaratan Rakyat Melantik Presiden Dan Wakil Presiden - Talakua, Petra; Nendissa, Reny Heronia; Irham, Muhammad (Pusat Studi Hukum dan Pemerintahan Fakultas Hukum Universitas Pattimura, 2025)
The authority of the MPR in inaugurating the President and Vice President is the only thing that is routinely done every 5 years since the amendment of the 1945 Constitution, which in its implementation tends to be merely ceremonial. Some of the MPR's constitutional powers do not yet have legal regulations, one of which is the authority to appoint the President and Vice President. So far, the appointment of the President and Vice President has only been carried out by reading the Decision from the KPU by the MPR RI leadership, leading many parties to question the legality of the MPR in appointing the President and Vice President. This research aims to analyze the plenary session process of the inauguration of the President and Vice President, regarding the authority of the MPR in inaugurating the President and Vice President as regulated in Article 3 Paragraph (2) of the 1945 Constitution of the Republic of Indonesia. Then, this research aims to analyze the legal strength of the inauguration minutes of the President and Vice President as the legal basis for their appointment. The normative legal research method involves primary and secondary legal sources and a legislative approach that focuses on the analysis and examination of legal regulations. The researcher uses primary and secondary data collection techniques in the form of laws and legal books, expert opinions, and legal journals. This research provides input to the MPR to issue a decree in the form of a decision (beschikking) regarding the determination of the winning pairs of presidential and vice-presidential candidates in the election as the President and Vice President of the Republic of Indonesia for the next five-year term, so that the President and Vice President have a stronger legal basis in the form of an MPR decree.